Analytical investigation into the effects of nitrogen enriched air bubbles to improve aircraft fuel system water management - Terada, Yuri; Lawson, Craig P.; Zare Shahneh, Amir (SAGE, 2017)
In the aircraft fuel system, water–ice contamination within fuel tanks has been one of the most serious challenges. This issue was highlighted in 2008 by an accident triggered by restricted fuel flow due to the ice formation within the system. The on-board inert gas generation system, which is already installed on some aircraft to prevent the outbreak of fire in the fuel tank, is a potentially feasible method to improve the water management. This paper focuses on the impact of bubbles from the on-board inert gas generation system system on water in the fuel tank. In order to explore the bubble effect, the relationship between orifice configuration and bubble parameter was investigated by means of mathematical models and existing experimental data. Moreover, by combining a MATLAB code and the introduced bubble model, the effect of bubble size and rising speed on the water contamination in the fuel tank was observed. For the water absorption process, a new model was introduced using a mass transfer coefficient. Finally, this article concludes that the amount of accumulated water is dependent on the bubble size and rising speed, and an optimal bubble size or speed is predictable once the coefficient has been obtained.
Keywords: Aerospace; Aircraft; Water contamination; Fuel system; On-board inert gas generation system; Nitrogen-enriched air; Bubble